Status of the RFQ linac installation and conditioning of the Linear IFMIF Prototype Accelerator. (May 2018) - Shinya, Takahiro; Fagotti, E.; Weber, M.; Antoniazzi, L.; Akagi, T.; Bellan, L.; Bortolato, D.; Ebisawa, T.; Grespan, F.; Hirata, Y.; Ichimiya, R.; Kasugai, K.; et al.
Highlights: The RFQ linac and its RF power system were installed to the LIPAc facility. The eight RF chains provide the balanced RF power to the single RFQ cavity in-phase using a feedback loop and a synchronization system. The peak power in the cavity achieved 150 kW in the pulse mode, which corresponds approximately to the required electric field to accelerate proton beam. Abstract: The Radio Frequency Quadrupole (RFQ) linac and 1.6 MW RF power system of the Linear IFMIF Prototype Accelerator (LIPAc) facility in the International Fusion Energy Research Center (IFERC) in Rokkasho (Japan) has been installed and conditioned. During the assembly and tuning process, the RFQ cavity was protected with a temporary tent from the potential deterioration of performance caused by dust. The vacuum in the cavity was improved through the 100  °C baking process of the cavity. The high power test of the 175 MHz RF systems up to 200 kW in CW for each of the eight RF chains was performed for checking its stable output reproducibility in Japan, before connecting 9–3/16 inch coaxial transmission lines from the RF chains to the RF input couplers of the cavity. It was confirmed that the eight RF chains provided the balanced RF power to the single RFQ cavity in-phase using a feedback loop and a synchronization system. The peak power in the cavity achieved 150 kW in the pulsed mode, which corresponds approximately to the required electric field to accelerate proton beam. Such RF conditioning process is ongoing to achieve 600 kW approximately required for deuteron beam commissioning planned in 2018.